How is Coronavirus Crisis Changing International Business? - Danko, Taras (My University, 2020)
The coronavirus crisis is dramatically changing lifestyles, markets, workplaces, business processes and value chains. The coronavirus challenges for international business include employee safety, financial sustainability, the resilience of supply chains, crucial systems maintenance to support, unprecedented levels of remote working and online trading, swift global markets transformation, and new COVID-19 legislation. Consequently, international firms are changing at an enormous speed, developing new essential capabilities, many of which are based on Industry 4.0 technologies.
Keywords: international business; fourth industrial revolution; cluster organizations; re-globalization; e-internationalization; innovation ecosystems; capabilities